IMPLEMENTASI PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI DALAM MENGATASI KEMISKINAN PERKOTAAN DI KECAMATAN NUSANIWE, KOTA AMBON - Rahakbauw, Nancy (Jurnal Insani, 2015)
This study aims to to understand the process of beneficiaries and the direct impact of a government program of PNPM Mandiri P2KP as an attempt to improve the welfare of the community, in terms of environmental, economic and social held in District Nusaniwe, Ambon.PNPM Mandiri P2KP is empowerment program for people who are not economically able to pay for his life and lived in the house uninhabitable. The process is carried out to provide assistance to beneficiaries are those who fall into the category of poor that are listed in the list of poor people or people can not afford. In addition, the PNPM Mandiri P2KP beneficiaries are citizens who are impaired in terms of transportation such as roads dan bridges that impede their access to improve their welfare. Programs provided by the government is more focused on environmental, economic and social.Based on the findings, the impact is felt by beneficiaries of government aid is no increase in the welfare of both individuals and society, and hoped that similar programs could be improved further.